Theologia Sistematika sebagai Bahan Khotbah bagi Pembinaan Warga Gereja - Nuban, Eliazer; Banfatin, Nahor; Adilang, Ryanto (Sekolah Tinggi Teologi Parakletos Tomohon, 2025)
Abstract: Sermons need to be equipped with a strong foundation of the Word through systematic doctrine so that the preaching of God's Word can be conveyed and transform the faith of every believer. Therefore, the purpose of this article is to examine Systematic Theology is a discipline whose truth is systemized, structured, which comes from the teaching of the Bible which is the Word of God. Thus, if someone learns from the Bible regularly, it will have implications for the discovery of the truth about Christian doctrine which has an impact on the church to do systematic theology which can be integrated with preaching services, (Homiletics) for the development of church citizens. The approach used is descriptive qualitative with a literature study method where researchers review books and articles related to systematic theology and homiletics. The results of this study are expected to overcome the gap by making Systematic Theology through thematic aspects as preaching material so that the development of church members will run well because Systematic Theology comes from the Bible which is the Word of God. The implications of this research encourage preachers to preach systematically which has an impact on the congregation's transformative understanding of the Christian Faith. Abstract: Khotbah perlu diperlengkapi dengan dasar Firman yang kuat melalui doktrin yang sistematis agar pemberitaan Firman Tuhan dapat tersampaikan serta mentransformasi iman setiap orang percaya. Oleh karena itu, tujuan artikel ini adalah mengkaji Theologi Sistematika merupakan disiplin ilmu yang kebenarannya tersistem, terstruktur, yang bersumber dari pada pengajaran Alkitab yang adalah Firman Allah. Dengan demikian jika seseorang belajar dari Alkitab secara teratur akan berimplikasi pada penemuan kebenaran terhadap doktrin Kristen yang berdampak kepada gereja untuk bertheologi secara sistematika yang dapat diintegrasikan dengan pelayanan berkhotbah bagi pembinaan warga gereja. Pendekatan yang digunakan adalah kualitatif deskriptif dengan metode studi literatur dimana peneliti mengkaji dari buku dan artikel terkait dengan teologi sistematika dan homiletika. Hasil penelitian ini diharapkan untuk mengatasi kesenjangan dengan menjadikan Theologia Sistematika melalui aspek tematis sebagai bahan khotbah, agar pembinaan warga gereja akan berjalan dengan baik karena Theologia Sistematika bersumber dari Alkitab yang adalah Firman Allah. Implikasi dari penelitian ini mendorong pengkhotbah untuk berkhotbah secara sistematis yang berdampak pada pemahaman transformatif jemaat terhadap Iman Kristen.